(untitled) (Journal of Academic Research, 2024)
The research aims to study and analyze spending on education and measure its impact on human development in Libya during the period 1990-2012, the research relied on the descriptive analytical method to describe the educational system in Libya, and analyze the evolution of spending on education and the development index of Libya during the period under research, and the impact of the relationship of independent variables on the dependent variable was measured Using the Autoregressive Distributed Lag model (ARDL) to estimate the impact of independent variables on the dependent variable by the Eviews 10 program, based on the research hypothesis that Increasing spending on education leads to human development, and the research reached several results, the most important of which are: Libya was often classified according to the Human Development Index from countries with medium achievement, the ratio of spending on education to public expenditure and its ratio to GDP remained weak throughout the period under research, and the results of the model’s estimate showed a long-term relationship to spending on education in Libya on the Human Development Index, In addition, there is a relationship with a positive and significant impact of economic growth on the human development index and a relationship with an adverse and significant impact of unemployment on the human development index, moreover, the error correction coefficient (ECM) showed the speed of correction towards long-term equilibrium by (1.55).